Sorption discrimination between secondary alcohol enantiomers by chiral alkyl-dicarboxylate MOFs. Issue 96 (30th September 2016) - Satska, Yulia A.; Mikhalyova, Elena A.; Chernenko, Zhanna V.; Kolotilov, Sergey V.; Zeller, Matthias; Komarov, Igor V.; Tymtsunik, Andriy V.; Tolmachev, Andrey; Gavrilenko, Konstantin S.; Addison, Anthony W.
Abstract : The coordination polymers with trans -( S, S )-1, 2-cyclopropane dicarboxylate or (1 R, 3 S )-camphorate contain only one polar group in close proximity to the asymmetric C atom but show different sorption of ( R ) or ( S ) isomers of 2-butanol. Abstract : The 3D coordination polymer [Co2 (H2 O)(cpda)2 (py)4 ·py] n (cpdaH2 is trans -( S, S )-1, 2-cyclopropane dicarboxylic acid, py = pyridine) crystallizes from pyridine as 1 ·5py (one py is not coordinated) and was characterized by X-ray single crystal diffraction. Desolvation of 1 ·5py was accomplished with decoordination of pyridine and transformation of the Co II octahedral coordination into tetrahedral, as confirmed by electronic spectroscopy. Sorption of individual optical isomers – ( S )-2-butanol and ( R )-2-butanol – from the gas phase at 303 K by desolvated 1 was studied, and for comparison sorption of these substrates by the chiral MOFs [Zn2 (camph)2 (bipy)] n (2 ) and [Zn2 (camph)2 (dpe)] n (3 ) was examined (camphH2 is (1 R, 3 S )-camphoric acid, bipy is 4, 4′-bipyridine, dpe is trans -1, 2-di(4-pyridyl)ethylene). Chiral sites in 1–3 contain only one polar group (carboxylate) in close proximity to the asymmetric C atom, while the other groups contain only C–H or C–C bonds. In the cases of 1 or 2 the absorption isotherms grew abruptly at certain pressure values P, and these values were different for the ( R ) or ( S ) isomers' sorptions. Such differential growth can be accounted for through the polymeric framework's rearrangement induced by interaction with 2-butanol, the difference in P values for ( R ) and ( S ) isomers being an indication of different interaction energies for these isomers with the MOF. There was no significant difference between the values of total sorption capacity of 1 for the two enantiomers of 2-butanol at pressures close to the saturation vapor pressure. In contrast, the sorption capacity of 3 was higher for ( R )-2-butanol than for ( S )-2-butanol over the whole pressure range.